Students' multimodal construction of work-energy concepts - Tang, Kok-Sing; Tan, S.; Yeo, J. (Routledge, 2011)
This article examines the role of multimodalities in representing the concept of work–energy by studying the collaborative discourse of a group of ninth-grade physics students engaging in an inquiry-based instruction. Theorising a scientific concept as a network of meaning relationships across semiotic modalities situated in human activity, this article analyses the students’ interactions through their use of natural language, mathematical symbolism, depiction, and gestures, and examines the intertextual meanings made through the integration of these modalities. Results indicate that the thematic integration of multimodalities is both difficult and necessary for students in order to construct a scientific understanding that is congruent with the physics curriculum. More significantly, the difficulties in multimodal integration stem from the subtle differences in the categorical, quantitative, and spatial meanings of the work–energy concept whose contrasts are often not made explicit to the students. The implications of these analyses and findings for science teaching and educational research are discussed.